Efektifitas Kompetensi Dalam Meningkatkan Kinerja Pegawai - Ansori, Putra Budi; Risman, Risman (Eko dan Bisnis: Riau Economic and Business Review, 2023)
The purpose of this study was to determine the effect of competence on the performance of. To achieve this goal, a study was conducted using a sample of 68 people, using the census method. Methods of data analysis using simple linear regression. Based on the results of partial t-test testing, it was found that competency had a significant effect on the Performance, this was proven based on the t-test found that t-count was greater than t-table (2.707 > 1.997). The magnitude of the influence of the competency variable on employee performance variables is 0.51.3 (51.3%) this is proven based on the results of the determination test where an R2 value of 0.513 is obtained. Recommendations that can be submitted It is expected that the work assigned to employees must be in accordance with their expertise because this gets the lowest response from respondents